Exploiting tumor metabolism: challenges for clinical translation - Vander Heiden, Matthew G. (American Society for Clinical Investigation, 2013)
The metabolism of cancer cells differs from most normal cells, but how to exploit this difference for patient benefit is incompletely understood. Cancer cells require altered metabolism to efficiently incorporate nutrients into biomass and support abnormal proliferation. In addition, the survival of tumor cells outside of a normal tissue context requires adaptation of metabolism to different microenvironments. Some existing chemotherapies target metabolic enzymes, and there is a resurgent interest in developing new cancer drugs that interfere with metabolism. Success with this approach depends on understanding why specific metabolic pathways are important for cancer cells, determining how best to select patients, and developing technologies for monitoring patient response to therapies that target metabolic enzymes. The articles in this Review series address these issues, with a focus on how altered metabolism might influence tumor progression and how this knowledge might inform the use of new therapies targeting cancer metabolism. Emerging biomarker strategies to guide drug development are also highlighted.